Optimal Income Tax Deductions for Mixed Business and Personal Expenditures - Jacob Goldin; Sebastian Koehne; Nicholas Lawson (CESifo GmbH, 2024)
We study the optimal taxation of expenditures that generate income while also serving a consumption function. We characterize the Pareto optimal income tax deduction for such mixed-purpose expenditures within a generalized Atkinson-Stiglitz model. Pareto optimality requires a partial deduction for mixed-purpose expenditures, where the deduction rate depends on the fraction of an expenditure's marginal benefits that are attributable to income-generation rather than consumption. We extend our results to account for several practical considerations, including potential constraints relating to a uniform deduction rate or a fixed income tax schedule. Our results provide a rationale for non-uniform commodity taxation, distinct from existing models of preference heterogeneity or non-separability.
Keywords: D82; H21; 330; optimal taxation; tax deduction